Problematyka ochrony środowiska na przygranicznych terenach zachodniej Polski w opinii wójtów i burmistrzów małych miast - Mickiewicz, Antoni; Mickiewicz, Bartosz; Orylska, Jadwiga (Problematics of Environment Protection on the Border Land of Western Poland in Small Cities Mayors' Opinion, 2005)
The aim of the paper is a presentation of problematics of environment protection on the border land of Western Poland in small cities mayors' opinion. There are published advancements of parishes association about natural environment protection in 2004-2006 in the article. The projects concerne the plan of investments financing realization by the Coherity Funds from the European Union. In tables there are presented mayors' opinion about the problems of the natural environment protection. It is expected that realization of proposed projects in Western Pomeranian province will improve the state of the environment and influence favourably the health of population living on the border land.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 85-91